Pengaruh Tingkat Inflasi, BI-7 Day Reverse Repo Rate Laba Bersih dan Firm Size terhadap Harga Saham pada Industri Sub Sektor Kosmetik dan Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Atikah Atikah (Universitas Batanghari Jambi, 2022)
This study aims to describe the formulation of the problem that has been designed,Namely to analyzed the effect of Inflation Rate, BI-7 Day Reverse Repo Rate, Net Profit and Firm Size simultaneously and partially on stock prices in the cosmetics and household goods sub-sector industry registered at Bursa Efek Indonesia period 2016-2020. The research methodology used is descriptive analysis method and statistical analysis method. The data used is secondary data. Based on the simultaneous test of ftable (3,091>2,76), by comparing the level of significance 0,034>0,05, so that it can be interpreted that simultananeosly the variable inflation rate, BI-7 day reverse repo rate, net profit, and firm size the effect stock prices. Based on the partial test, it can be concluded that the inflation rate variable has no positive and insignificant effect on stock prices, where thitung is 0.919 dan ttable 2,05954 (0,919<2,05954) with a significant level comparison (0,367>0,05), The BI-7 day reverse repo rate variable has no negative and insignificant effect on stock price, where thitung -0,598 dan ttabel 2,05954 (0,598<2,05954),with a significant level comparison (0,555>0,05), Net Profit variable is known to have a positive and significant effect on stock price, where thitungnya 2,814 and ttabel 2,05954 (2,814>2,05954) with a significant level comparison (0,009<0,05), and firm size variable firm has a negative and significant effect on stock, where thitungnya -3,441 and ttabel 2,05954 (3,441<205954) with a significant level comparison (0,002<0,05). The results of the coefficient of determination in this study indicate that the R Square is 0,331 which means that the contribution of the independent variable affects the dependent variable in this study of (0,331x100=33,1%).